Implementasi Model Pembelajaran Make A Match Berbasis Kearifan Lokal Untuk Meningkatkan Hasil Belajar Kognitif Siswa - Jayanik Mayasari; Murtono Murtono; Imaniar Purbasari (Journal on Education, 2020)
Education cannot be interpreted only as science implementation , but it is broader. By implementing proper education, learners will also understand local wisdom in their surrounding environment. This research takes local wisdom in Kudus as Hindu, Buddist, and Islam heritages. This research aim to find out the implementation of Make A Match learning model based on local wisdom toward the cognitive learning outcames of learners. This research applice classroom action method promoted in two cycles. Each cycle consisted of four stages: 1) planning; 2) acting; 3) observing; 4) monitoring. The finding showed that Make A match model based on local wisdom could improve cognitive leraners’ learning outcames. It could be seen from the reached indicators as follow. Cognitive learning outcame improvement improved with a pre-cycle score achievement of social suty lesson 52,63% it improved into 68,42% in cycle I then, it improved in cycle II 84,21%. Meanwhile, dealing with Indonesian language content, it improved from 68,15% in pre-cycle into 73,6% in cycle I then, in cycle II it improved into 89,47% Keywords: Learning Outcomes, Make A Match, Local wisdom